Strengthening digital literacy and political culture for gen-Z through Pancasila education learning in higher education - Muhajir; Abdul Latief; Monica Tiara (Universitas Negeri Yogyakarta, 2025)
This article reviews the importance of political culture and digital literacy for Generation Z as a prospective demographic group. It examines how Pancasila education contributes to the development of Gen-Z's political culture and literacy in higher education. Using a mixed-method research approach with a sequential transformative strategy model, the study transforms one type of data into another after collecting and analyzing quantitative and qualitative data independently. Research findings indicate that trending topics, viral hashtags, FYP, news feeds, CC, and social media algorithms form the foundation of Gen-Z's digital political literacy and culture. This illustrates that, despite avoiding direct practice, Gen-Z exhibits a keen interest in digital politics. Consequently, Pancasila education provides Gen-Z members with opportunities to become competent political players and participants. The study also shows how Pancasila education incorporates digital-based political literacy and culture by emphasizing civic duties and integrating more